Design of functionalized double-metal MXenes (M2M'C2T2: M = Cr, Mo, M' = Ti, V) for magnetic and catalytic applications. (19th May 2022) - Geng, Jiazhong; Wu, Rucheng; Bai, Haoyun; Chan, Iat-Neng; Ng, Kar Wei; Ip, Weng Fai; Pan, Hui
Abstract: Two dimensional (2D) materials have demonstrated huge potential in wide applications ranging from nanodevices to energy storage. In this work, we propose a series of double-metal MXenes functionalized with various terminal atoms (M2 M'C2 T2 ), including B, N, O, P and S, based on density-functional theory (DFT) calculation. We screen out a series of stable structures and study their magnetic and electronic properties. We find that the magnetism of M2 M'C2 T2 can be regulated according to different transition metals and terminal atoms. The magnetic moments of Cr2 TiC2 T2 and Cr2 VC2 T2 (T = N, O or S) are mainly contributed by chromium, while those of Mo2 VC2 T2 (T = N, O or S) are originated from vanadium. We also find that these monolayers are metal with spontaneous conductivity, which is favorable for the electrocatalysis. The Gibbs free energies for the adsorption of hydrogen atoms on Cr2 TiC2 S2, Cr2 VC2 S2 and Mo2 TiC2 P2 are close to zero, indicating their high catalytic activity for hydrogen evolution reaction (HER). Our findings suggest that the functionalized double-metal MXenes are promising materials for magnetic nanodevices and electrocatalysts. Graphical abstract: Image 1 Highlights: A series of double-metal MXene functionalized with B, N, O, P and S are proposed. The magnetism of M2 M'C2 T2 varies with their composition. Cr2 TiC2 S2, Cr2 VC2 S2 and Mo2 TiC2 P2 exhibit high electrocatalytic activity for HER.